Síntese e caracterização de filmes de polietileno/poli(álcool vinílico) contendo nanopartículas de negro de fumo e sílica - Vieira, Pedro Henrique da Costa (2016)
High density polyethylene (HDPE) is widely used in the production of automobile fuel tanks due to low density and processability, despite being permeable to organic solvents. In order to improve their barrier properties, the aim of this work was study the synthesis and characterization of HDPE and poly (vinyl alcohol) (PVA) mixtures, and verify the effect of crosslinking of PVA with maleic anhydride (MAH) and the presence of carbon black (NF) and silica (SIL) nanoparticles. The films were produced by solubilization of polymers, then dried and compressed at high temperature. To understand in a better way the structure-properties relation, the films were characterized by infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA) and scanning electron microscopy (SEM). Their transport properties were determined by swelling and pervaporation tests, and the results are discussed in terms of the basic mechanism of sorption-diffusion. A binary model organic solution was used as a gasoline model in the permeability tests. There was obtained HDPE/PVA films crosslinked with 30% reductions in the permeate flow, films with 3% NF reached 45% barrier, while films with 1% silica achieved 18% increase in barrier organic solvents, compared with the flow of HDPE films.